Interaction between an entomopathogenic fungus and entomopathogenic nematodes for increased mortality of Thaumatotibia leucotreta (Lepidoptera: Tortricidae). Issue 10 (3rd October 2022) - Prinsloo, Samantha; Hill, Martin P.; Moore, Sean D.; Malan, Antoinette P.; Coombes, Candice A.
ABSTRACT: Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is a major phytosanitary pest of citrus in South Africa. Although several management tools exist, control options registered for use against the soil-dwelling life stages are limited . Both entomopathogenic nematodes (EPNs) and entomopathogenic fungi have been investigated previously, but they have not been studied in combination against T. leucotreta . Thus, this study investigated the interaction of an indigenous entomopathogenic fungus, Metarhizium pinghaense (previously anisopliae ) FCM Ar 23 B3 with three indigenous EPNs: Steinernema yirgalemense 157-C, S. jeffreyense J194 and Heterorhabditis noenieputensis 158-C for increased late instar T. leucotreta larval mortality. Before interaction experiments, lethal concentration (LC) values for each of these microbial agents were determined through dose–response bioassays. Heterorhabditis noenieputensis recorded the highest LC50 amongst the nematodes (7.11 IJs/50 µl). Using the pre-determined LC70 value of M. pinghaense and the LC50 values for each of the nematode species, interaction experiments were conducted. Combinations of the nematodes either applied simultaneously with the fungus or at 24, 48, 72 or 96 h post-fungal application showed predominantly additive interactions. Synergy between the simultaneous application of S. yirgalemense and M. pinghaense was found, whilst the interaction between H. noenieputensis and M. pinghaense applied simultaneously and S. jeffreyense applied 24 h post-fungal application, recorded antagonistic interactions. The use of these agents in combination may therefore have the potential to increase control of T. leucotreta soil-dwelling life stages in citrus orchards across South Africa and should be further investigated.